Facing instability: Subsistence and adaptation strategies of two artists from Lima in the view of job insecurity - Reynoso Gálvez, Micaela (2022)
In this article, we discuss the cases of two artists from Lima, focusing on the strategies they develop to confront institutionalized job insecurity. It is argued that such insecurity is due to the nature of a national art system co-opted by the elites and the State, in which external actors are left aside. Plus, this phenomenon is caused by the capitalist mode of production that frames the artistic labor in a specific way and logic. After carrying out fieldwork during June and July 2021, it is proposed that strategies can be analysed from four different axes: market relations, institutional and/or governmental support, use of social networks and cooperation networks with other colleagues. To achieve analytical depth, we put this empirical data in dialogue with the theoretical approaches that come from anthropology of art and studies of job insecurity and strategies developed by individual actors. Following a material perspective, we read these cases as embedded within a national art system that conditionates specific social and material foundations.